P107 Who has dreams fulfilled at end of life? An audit of a dream fulfilment organisation for children and young people. (1st October 2013) - Galinsky, Jayne; Forbat, Liz; France, Emma; White, Jane
Abstract : Dream fulfilment provides a positive focus, hope and a sense of future for children and young people whose lives may be filled with hospital visits, pain or worry. This paper will present the results of an audit of a dream fulfilment charity's database. The audit systematically analyses user demographics to find out more about who uses charities such as these. This project fits with the strategic exercise conducted by the NHS in England to 'map' palliative care services across England so that both health professionals and the public can see what services are, and where they are available. The data reported in this paper are drawn from Dreams Come True's records of children and young people with life limiting and long term conditions and their families, and the dreams that they have had. Descriptive statistics are used to summarise the clinical and socio-demographic characteristics of the children/ families who have used the charity's services over the last five years. Results highlight the range of health conditions that children who use the charity have, as well as reporting on other factors such as the child's age, family size, gender and the type of dream requested. Analysis also suggests gaps in service reach which may reflect the unmet need in the sector as a whole. Results will be of interest to health care professionals working in the fields of paediatric palliative care, and care of children with long term conditions, as well as to other dream fulfilment charities. The audit's findings have implications for referring organisations, such as hospices, and potential lessons for the adult sector.